All roads lead to Rome: inter-origin variation in metabolomics reprogramming of the northern shrimp exposed to global changes leads to a comparable physiological status - Guscelli, Ella; Chabot, Denis; Vermandele, Fanny; Madeira, Diana; Calosi, Piero (Frontiers in Marine Science, 2023)
Impacts of global ocean changes on species have historically been investigated at the whole-organism level. However, acquiring an in-depth understanding of the organisms’ cellular metabolic responses is paramount to better define their sensitivity to environmental challenges. This is particularly relevant for species that experience highly different environmental conditions across their distribution range as local acclimatization or adaptation can influence their responses to rapid global ocean changes. We aimed at shedding light on the cellular mechanisms underpinning the sensitivity to combined ocean warming (OW) and acidification (OA) in the northern shrimp Pandalus borealis, from four different geographic origins defined by distinctive environmental regimes in the northwest Atlantic: i.e. St. Lawrence Estuary (SLE), Eastern Scotian Shelf (ESS), Esquiman Channel (EC) and Northeast Newfoundland Coast (NNC). We characterized targeted metabolomics profiles of the muscle of shrimp exposed to three temperatures (2, 6 or 10°C) and two pH levels (7.75 or 7.40). Overall, shrimp metabolomics profiles were modulated by a significant interaction between temperature, pH and origin. Temperature drove most of the metabolomics reprogramming, confirming that P. borealis is more sensitive to OW than OA. Inter-origin differences in metabolomics profiles were also observed, with temperature*pH interactions impacting only shrimp from SLE and ESS, pH affecting only shrimp from SLE and temperature impacting shrimp from all origins. Temperature influenced metabolomics pathways related to the tricarboxylic acid cycle (TCA) and amino acid metabolism, resulting mainly in an accumulation of TCA intermediates and tyrosine. Temperature*pH and pH in isolation only affected amino acid metabolism, leading to amino acids accumulation under low pH. However, the ratio of ATP : ADP remained constant across conditions in shrimp from all origins suggesting that their energetic status is not affected by OW and OA. Still, the accumulation of TCA intermediates and tyrosine suggests the possible enhancement of immune responses under future OW and OA conditions. Our findings suggest that shrimp from SLE are more sensitive at the molecular level, compared to others, to future complex environmental conditions. This underlines the importance of investigating intraspecific variation in mechanisms of responses to combined drivers when trying to define species’ sensitivity to global ocean changes.